Rapid Health Evaluation of Analgesia with Long-Acting Local Anesthesia After Hip and Knee Arthroplasty - Zhang X; Li M; Lei L (Integrated Pharmacy Research and Practice)
Xiaoyue Zhang, Mengting Li, Luwen Lei Department of Pharmacy, Department of The Sixth Affiliated Hospital, School of Medicine, South China University of Technology, Foshan, People’s Republic of ChinaCorrespondence: Luwen Lei, Email leiluwen618@163.comPurpose: To evaluate the local anesthetic drugs commonly used after hip arthroplasty and knee arthroplasty, and to provide a reference for clinical drug use and drug selection in medical institutions.Methods: Based on the “Quick Guide for Drug Evaluation and Selection in Chinese Medical Institutions (Second Edition)”, the included drugs were evaluated from five dimensions of pharmaceutical properties, effectiveness, safety, economy, and other attributes using a 100-point scoring method.Results: The quantitative scoring results were ranked from high to low as Dishili-Ropivacaine injection (75 points), Naropin-Ropivacaine injection (68.97 points), liposomal bupivacaine (65.06 points), bupivacaine injection (61.05 points), and levobupivacaine injection (60.35 points).Conclusion: The Dishili-Ropivacaine injection of the collectible variety is a strongly recommended variety, which is recommended to be introduced or retained in the drug catalog of medical institutions, and the Naropin-Ropivacaine injection and liposomal bupivacaine can be adjusted according to the actual situation and clinical needs of medical institutions.Keywords: local anesthetic drugs, local anesthetics, drug selection, rapid health evaluation, postoperative analgesic